PENGARUH KONFLIK INTERPERSONAL, BEBAN KERJA, DAN KEMAMPUAN KERJA TERHADAP STRES KERJA KARYAWAN (STUDI KASUS PADA RB TV DI KOTA BENGKULU) - Aprizon, Aprizon; Onsardi, Onsardi (UM. Bengkulu, 2025)
This research aims to determine the influence of interpersonal conflict, workload and work ability on employee work stress. There are several factors that will be discussed in this research, including Interpersonal Conflict, Workload, and Work Ability. In this research the author used data collection methods by means of observation, distributing questionnaires and interviews. The results of the study prove that Interpersonal Conflict has a positive and significant effect on work stress. Workload has a positive and significant effect on work stress. Work Ability has a negative effect on work stress. Interpersonal conflicts, workload and workability have a positive and significant effect on employee work stress at RBTV in Bengkulu City.Keywords : Interpersonal Conflict, Workload, Work Ability, Employee Work Stress.